Cryotherapy in sports medicine - Swenson, C.; Sward, L.; Karlsson, J. (Scandinavian Journal of Medicine & Science in Sports, 1996)
The use of cryotherapy, i.e. the application of cold for the treatment of injury or disease, is widespread in sports medicine today. It is an established method when treating acute soft tissue injuries, but there is a discrepancy between the scientific basis for cryotherapy and clinical studies. Various methods such as ice packs, ice towels, ice massage, gel packs, refrigerant gases and inflatable splints can be used. Cold is also used to reduce the recovery time as part of the rehabilitation programme both after acute injuries and in the treatment of chronic injuries. Cryotherapy has also been shown to reduce pain effectively in the post-operative period after reconstructive surgery of the joints. Both superficial and deep temperature changes depend on the method of application, initial temperature and application time. The physiological and biological effects are due to the reduction in temperature in the various tissues, together with the neuromuscular action and relaxation of the muscles produced by the application of cold. Cold increases the pain threshold, the viscosity and the plastic deformation of the tissues but decreases the motor performance. The application of cold has also been found to decrease the inflammatory reaction in an experimental situation. Cold appears to be effective and harmless and few complications or side-effects after the use of cold therapy are reported. Prolonged application at very low temperatures should, however, be avoided as this may cause serious side-effects, such as frost-bite and nerve injuries. Practical applications, indications and contraindications are discussed. : Scand J Med Sci Sports 1996 Aug;6(4):193-200